Risk Factors and Molecular Epidemiology of Complicated Intra-Abdominal Infections With Carbapenem-Resistant Enterobacteriaceae: A Multicenter Study in China. (16th March 2020) - Liu, Jiao; Zhang, Lidi; Pan, Jingye; Huang, Man; Li, Yingchuan; Zhang, Hongjin; Wang, Ruilan; Zhao, Mingyan; Li, Bin; Liu, Long; Gong, Ye; Bian, Jinjun; et al.
Abstract: Background: Carbapenem-resistant Enterobacteriaceae (CRE) infections are associated with poor patient outcomes. Data on risk factors and molecular epidemiology of CRE in complicated intra-abdominal infections (cIAI) in China are limited. This study examined the risk factors of cIAI with CRE and the associated mortality based on carbapenem resistance mechanisms. Methods: In this retrospective analysis, we identified 1024 cIAI patients hospitalized from January 1, 2013 to October 31, 2018 in 14 intensive care units in China. Thirty CRE isolates were genotyped to identify β-lactamase-encoding genes. Results: Escherichia coli (34.5%) and Klebsiella pneumoniae (21.2%) were the leading pathogens. Patients with hospital-acquired cIAI had a lower rate of E coli (26.0% vs 49.1%; P < .001) and higher rate of carbapenem-resistant Gram-negative bacteria (31.7% vs 18.8%; P = .002) than those with community-acquired cIAI. Of the isolates, 16.0% and 23.4% of Enterobacteriaceae and K pneumoniae, respectively, were resistant to carbapenem. Most carbapenemase-producing (CP)-CRE isolates carried blaKPC (80.9%), followed by blaNMD (19.1%). The 28-day mortality was 31.1% and 9.0% in patients with CRE vs non-CRE ( P < .001). In-hospital mortality was 4.7-fold higher for CP-CRE vs non-CP-CRE infection ( P = .049). Carbapenem-containing combinations did not significantly influence in-hospital mortality of CP and non-CP-CRE. The risk factors for 28-day mortality in CRE-cIAI included septic shock, antibiotic exposure during the preceding 30 days, and comorbidities. Conclusions: Klebsiella pneumoniae had the highest prevalence in CRE. Infection with CRE, especially CP-CRE, was associated with increased mortality in cIAI.